The Impact of Percent Reduction in CA-125 Levels on Prediction of the Extent of Interval Cytoreduction and Outcome in Patients With Advanced-Stage Cancer of Müllerian Origin Treated With Neoadjuvant Chemotherapy. Issue 5 (June 2015) - Mahdi, Haider; Maurer, Kathryn A.; Nutter, Benjamin; Rose, Peter G.
Abstract : Objective: To investigate the role of CA-125 percent reduction after neoadjuvant chemotherapy in predicting the extent of the interval debulking surgery (IDS) and outcomes in patients with advanced-stage müllerian carcinoma. Methods: Patients who received neoadjuvant chemotherapy for advanced-stage müllerian carcinoma from 2000 to 2013 were identified. Percent reduction in CA-125 was categorized into 2 groups: ≥90% (CA ≥ 90%) and <90% (CA < 90%) reduction from prechemotherapy to preoperative CA-125. Results: Of the 115 patients identified, 73% had CA ≥ 90% and 27% had CA < 90%. Optimal and complete IDS were achieved in 87% and 38%, respectively. Compared with the CA < 90% group, the CA ≥ 90% group was more likely to have complete IDS ( P = 0.035), less likely to have a bowel resection ( P < 0.001), and more likely to have no viable tumor/microscopic disease with treatment effect ( P < 0.001). No difference in overall survival (OS; P = 0.81) and progression-free survival (PFS; P = 0.60) was noted between the groups. In multivariable analysis, CA ≥ 90% was not a predictor of PFS (hazard ratio [HR], 1.08; 95% confidence interval [CI], 0.65–1.79; P = 0.77) or OS (HR, 1.45; 95% CI, 0.73–2.9; P = 0.29). Patients with preoperative CA-125 < 20 had significantly longer OS ( P = 0.05) and PFS ( P = 0.005) than did those with preoperative CA-125 ≥ 20. In multivariable analysis, preoperative CA-125 < 20 was a predictor of PFS (HR, 0.37; 95% CI, 0.20–0.66; P < 0.001) but not OS (HR, 0.64; 95% CI, 0.34–1.21; P = 0.17). Conclusions: A reduction in CA-125 of at least 90% is associated with complete IDS, favorable pathologic response, and fewer bowel resections. A preoperative CA-125 < 20 suggests improved outcome. These findings are helpful for treatment planning and patient counseling.